Performance Evaluation of Hadoop in Cloud for Big Data - Fakherldin, Mohammed; Aaker Targio Hashem, Ibrahim; Alzuabi, Abdullah; Alotaibi, Faiz (International Journal of Engineering and Technology, 2018)
Recent trends in big data have shown that the amount of data continues to increase at an exponential rate. This trend has inspired many researchers over the past few years to explore new research direction of studies related to multiple areas in big data. Hadoop is one of the most popular platforms for big data, thus, Hadoop MapReduce is used to store data in Hadoop distributed file systems. While, cloud computing is considered an excellent candidate for storing and processing the big data. However, processing big data across multiple nodes is a challenging task. The problem is even more complex using virtualized clusters in a cloud computing to execute a large number of tasks. This paper provides a review and analysis of the impact of using physical versus cloud cluster in the processing a large amount of data. This analysis has an impact on the processing in terms of execution time and cost of using each one of them. The result indicates that the use of cloud virtual machines helped better utilize the resources of the host computer.Â